Cost Minimization Based Multi Way Automatic Changeover - Giri, Anirban; Hazra, Debabrata (International Journal of Computer Sciences and Engineering, 2025)
This article proposes a Cost minimizing based multi-way automatic changeover. Use of automatic multi-way change over will reduce the waste of money and also reduce the use of non-renewable energy. This process can be able to find out the most profitable source at any instant of time and able to derive the load from that source. The proper uses of relay and micro controller system reduce the time of switching. The proper relay logic ensures the proper isolation between sources. Any error signal generated by the controller cannot affect on the isolation of the sources. An LED monitoring system makes the system user friendly. The proposed changeover can able to handle more than 2 sources. It can work considering under voltage protection and try to supply power uninterruptedly to the load. The changeover always tries as much as it can use the available renewable energy source to drive the load. The proposed system will never disconnect the load to the source at any condition.